Prophetic Accounting: Disquiet in The Era of Postmodernism - Banu Witono; Kurnia Rina Ariani; Rita Wijayanti (Riset Akuntansi dan Keuangan Indonesia, 2021)
This paper discusses accounting which is seen as a form of value-free ideology. This ideology will certainly follow the flow of thoughts and beliefs of the initiating figures. Moving on from the long journey of upheaval and struggles of western and eastern thought (orientalism vs occidentalism) as well as the dialectical dynamics of thinking among western nations (modernism vs postmodernism) in the realm of philosophy, sociology, methodology and even in practice. It is undeniable that the development of postmodernism in the western world has had a positive impact on the stretching of thinking of Muslim scientists and academics in formulating accounting that contains spiritual values of Divine and Prophethood. Accounting is more egalitarian and not gender biased. Accounting is able to stimulate human behavior into a condition of divine consciousness or God Consciousness as part of its "rebellion" over the reality of accounting that is developing in the capitalistic world.